1983
DOI: 10.1063/1.445556
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton induced fluorescence and ionization of carbon monoxide (B 1Σ+)

Abstract: The B 1Σ+ state of carbon monoxide was created by a two-photon absorption of 230 nm laser radiation. The B 1Σ+ state was identified by the positions of the Q branch 0–0 absorption band and the vibrational bands of B 1Σ+ → A 1Π fluorescence occurring after excitation. Collision-induced b 3Σ+ → a 3Π emission in the 350 nm region was also observed. The lifetimes of the B 1Σ+ → A 1Π and the b 3Σ+ → a 3Π emission were obtained as well as the self-quenching rate constants and the CO (B 1Σ)) quenching rate by N2. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…40,41 The second harmonic of an injection seeded Nd:YAG laser ͑Spectra-Physics/Larry Wolford Services͒ pumped a Continuum dye laser, and the dye laser output was doubled in a KDP crystal. The doubled output was then mixed with the YAG fundamental in KDP for probing through the B state near 230 nm, or with the dye laser fundamental in BBO for probing through the E state near 215 nm.…”
Section: Methodsmentioning
confidence: 99%
“…40,41 The second harmonic of an injection seeded Nd:YAG laser ͑Spectra-Physics/Larry Wolford Services͒ pumped a Continuum dye laser, and the dye laser output was doubled in a KDP crystal. The doubled output was then mixed with the YAG fundamental in KDP for probing through the B state near 230 nm, or with the dye laser fundamental in BBO for probing through the E state near 215 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Lines starting in rotational levels up to JЉ =76 in Љ = 0 and up to JЉ =47 in Љ = 1 can be assigned. CO͑B 1 ⌺ + , =0͒ state is weakly predissociative for J ജ 38, 27 Rottke and Zacharias 28 have reported that the rate of predissociation is J independent. The line intensity decrease in =1, J = 18, and J = 36 are also observed, which are due to the CO͑B 1 ⌺ + ͒ state predissociated by other states.…”
Section: A Co Rempi Spectrummentioning
confidence: 99%
“…Thus it is convenient to write the angular distribution in terms of the From Eqs. (21), (22), and (25) we see that the excitation probability is nonvanishing only when Q"=q, +q2+ . +q"=Of -0 =b,Q.…”
Section: Introductionmentioning
confidence: 76%
“…In fact, we may see from Eq. (25) that the tensor component elk'. is the n-photon rotational line factor similar to the one-photon case [19,11,18].…”
Section: Introductionmentioning
confidence: 99%